A comparison of counselling self-efficacy across social factors among e-counsellors in Malaysia - Asri, Alia Sarah; Nor Zainudin, Zaida; Wan Othman, Wan Norhayati; Mohamad Yusop, Yusni; Ahmad, Nor Aniza; Hassan, Siti Aishah (ASR Research India, 2022)
The increase in the need for e-counselling is apparent in recent years due to its convenience to provide counselling support from remote locations. Despite the increasing number of e-counsellors, few studies have been conducted especially in the Malaysian context that highlight e-counsellors’ self-beliefs when providing e-counselling. Thus, this study was conducted to identify the level of counselling self-efficacy among e-counsellors in Malaysia and identify whether there is a significant difference between social factors, namely age groups, education levels, years of counselling experience, counselling licensure and registration status, on self-efficacy levels. A simple random sampling method was employed to select 159 e-counsellors in Malaysia who have prior experience in e-counselling implementation using any online-based medium. Larson’s (1992) Counselling Self-Estimate Inventory was adapted for purpose of data collection in this study. The analyses used were independent sample t-test and one-way analysis of variance. The findings report that e-counsellors have moderate levels of counselling self-efficacy overall, where a high level for one of the sub-construct pertained to application of basic counselling skills. E-counsellors who completed postgraduate studies had higher self-efficacy compared to e-counsellors with a bachelor’s degree. Registered and licensed e-counsellors reported higher levels of counselling self-efficacy compared to their counterparts. No significant differences were found for e-counsellors across age groups and years of counselling experience. This study recommends for professional counselling bodies, supervisors and counselling educators to revise and improve the education and training for counsellors at all social levels, especially in highlighting the practices of e-counselling.